KEBERPERANAN KOMPENSASI DAN MOTIF BERPRESTASI DALAM PENINGKATAN KINERJA DOSEN (Studi Analitik Terhadap Dosen di Perguruan Tinggi Ilmu pendidikan ) - Mulyana, Yusep (Infoman's, 2010)
Lecturer duty have very strategic role and function in supporting the of reaching purpose of higher education, because of lecturer participation related to development of quality assurance in each management of higher education, therefore, development of High Teacher require management functioning send lecturer reach optimal performance, with quality either from the profession and also rank career facet.Firstly, Based on research finding is recommended some thingses, for example compensation which given require to be evaluated to can be adapted growth of increase of price of requirement of the family and lecturer, to increase compensation side achievement motif which received also require to give opportunity to lecturer for developing the creativity and ability in executing the management study and construction from various party sides, thereby enable reached by better lecturer performance. (lecturer participation related to development of quality assurance in each management of higher education)